Extraction and Partial Characterization of Collagen from Different Animal Skins - Ashok Mhaske, Disha Raut, Rupal Singh, Abin Mani and Jaswant Patel, Sadaf Quereshi* (Recent Research in Science and Technology, 2010)
Collagen is a wonder triple helix fibrous protein. Basically, it connects and supports other bodily tissues, such as skin, bone, tendons, muscles and cartilage. In fact, it makes up about 25% of the total amount of proteins. Collagen possesses great tensile strength. In the present investigation, three methods of collagen extraction were employed. Out of which the method of George and Chandrakasan (1996) proved to be a better method for collagen extraction in chicken and human skins. Regarding Goat and Buffalo skins, collagen was extracted using TCA method wherein the extracted fibrous protein got hydrolyzed, getting denatured therefore, a definite band pattern was not obtained. By comparing the electrophoretic profile of various animal skins, a definite band pattern can be obtained which will indicate differences in collagen structure thereby facilitating species and generic differentiation. <span style="line-height: 200%; font-family: ";Arial Narrow";,";sans-serif";; letter-spacing: -0.3pt; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: EN-SG; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-SG; mso-bidi-language: AR-SA;" lang="EN-SG">